Urologists’ and general practitioners’ knowledge, beliefs and practice relevant for opportunistic prostate cancer screening: a PRISMA-compliant systematic review - Estevan-Ortega, María; de la Encarnación Castellano, Cristina; Mendiola-López, Alberto; Parker, Lucy A.; Caballero-Romeu, Juan Pablo; Lumbreras, Blanca (Frontiers in Medicine, 2024)
Background Recent guidelines on opportunistic prostate cancer screening conclude that the decision to screen with prostate-specific antigen should be made by each patient individually together with the clinician. However, there is evidence of a lack of clinicians’ awareness of prostate cancer screening. This study sought to assess the recent evidence of clinicians’ knowledge, beliefs, and practice regarding opportunistic prostate cancer screening comparing urologists and generals practitioners. Methods A systematic search was conducted in 3 online databases: MEDLINE, Web of Science and EMBASE (from January 1, 2015, to January 9th, 2023). Studies that explored clinicians’ knowledge, beliefs, and practices regarding opportunistic prostate cancer screening were included. Studies were assessed for quality reporting according to the Strengthening the Reporting of Observational studies in Epidemiology guidelines. Results A total of 14 studies met the inclusion criteria: ten studies included primary care health professionals, three studies included urologists, and one study included both. Studies involving general practitioners showed a generally low level of awareness of the recommended uses of the test, and urologists showed a greater knowledge of clinical practice guidelines. General practitioners’ opinion of prostate-specific antigen was generally unfavourable in contrast to urologists’ who were more likely to be proactive in ordering the test. Less than half of the included studies evaluated shared-decision making in practice and 50% of clinicians surveyed implemented it. Conclusion General practitioners had less knowledge of prostate cancer risk factors and clinical practice guidelines in the use of PSA than urologists, which makes them less likely to follow available recommendations. A need to carry out education interventions with trusted resources based on the available evidence and the current guidelines was identified.